Etnometodologi study: Revealing Establishment and treatment of “indan” in Toraja culture - IRENE LOLONGAN; YOHANIS RURA; DARWIS SAID (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to determine the formation and treatment of Indian Toraja culture. This research is qualitative using an ethnomethodological approach. Data collection techniques were carried out by observation, interviews and documentation techniques. The ethnomethodological data analysis techniques used in this study are indexicality analysis, reflexivity analysis, contextual action analysis, and the presentation of common sense knowledge about social structure. The results of the study show that in the implementation of Toraja traditional ceremonies, there is a practice of debt and credit, where the gifts given arise from conscience and self-awareness to help each other to strengthen and strengthen kinship ties. There is no prior agreement, but gifts are given solely because of a family relationship and trust, there is no repayment period, and there are no benefits that follow. This is very contradictory to conventional debt practices, where it is illustrated that the practice of social debt at Toraja traditional ceremonies is full of more values of justice, compared to conventional debt practices